Diseño de un programa de capacitación de los emprendimientos asociativos de la agencia de desarrollo económico de la administración zonal Quitumbe del Distrito Metropolitano de Quito. - Chimbo Arteaga, Henry Geovanny (2011)
The main objective is the full identification of the human resource with the Associative Entrepreneurship through generation: commitments, efforts and development of entrepreneurship and in turn the human resource for knowledge, develop their skills, abilities and change their attitudes obtaining the necessary autonomy to take risks, reacting positively in solving problems, allowing improving the quality of life of people.